2017
DOI: 10.1186/s12984-017-0271-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal estimation of intramuscular Tibialis Anterior coherence during subacute spinal cord injury: relationship with neurophysiological, functional and clinical outcome measures

Abstract: BackgroundEstimation of surface intramuscular coherence has been used to indirectly assess pyramidal tract activity following spinal cord injury (SCI), especially within the 15-30 Hz bandwidth. However, change in higher frequency (>40 Hz) muscle coherence during SCI has not been characterised. Thus, the objective of this study was to identify change of high and low frequency intramuscular Tibialis Anterior (TA) coherence during incomplete subacute SCI.MethodsFifteen healthy subjects and 22 subjects with motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…We have used intermuscular coherence, which conveniently measures shared input to muscle pairs. By contrast, Bravo-Esteban et al (2014 , 2017 ) measured intramuscular coherence using paired recordings from the TA muscle. In spinal cord-injured subjects with incomplete lesions (ASIA C or D), they found significant coherence at lower frequencies (10–16 Hz) during brief voluntary contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used intermuscular coherence, which conveniently measures shared input to muscle pairs. By contrast, Bravo-Esteban et al (2014 , 2017 ) measured intramuscular coherence using paired recordings from the TA muscle. In spinal cord-injured subjects with incomplete lesions (ASIA C or D), they found significant coherence at lower frequencies (10–16 Hz) during brief voluntary contractions.…”
Section: Discussionmentioning
confidence: 99%
“…The variable function of such circuits may explain why ~10 Hz cortico-muscular coherence can occasionally be seen ( Raethjen et al 2002 ; Williams et al 2009 ). In incomplete spinal cord injury, Bravo-Esteban et al (2014 , 2017 ) demonstrated that cortico-muscular coherence around 10–16 Hz correlated with the degree of spasticity. It remains to be determined which subcortical neural structure generates low-frequency rhythmic activity.…”
Section: Introductionmentioning
confidence: 98%
“…A: Schematic of the experimental strategy used to screen the potential differential genes in the GEO database. B: The heatmaps generated by R language using the mRNA expression data of the SCI group and the sham group in GEO at 1 d, 3 Inhibition of autophagy neutralized the bene ts on the autophagic activity and cell viability after AMPK activation in the injured PC-12 cells with si-Fosl1 treatment but promoted in ammation and cell apoptosis. A: Cell viability was detected using CCK-8 kits in the control group and the CQ group.…”
Section: Figurementioning
confidence: 99%
“…Spinal cord injury (SCI) is a disastrous nerve trauma in the central nervous system (CNS) currently without su cient treatment options, which affects several millions people worldwide and leads to catastrophic complications [1,2], such as neurological de cits [3], paraplegia [4], osteoporosis [5], and others. These complications place huge psychological and physical burdens on patients and threaten their health and life quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a devastating event that can lead to neurological de cits and motor dysfunction [1][2]. The dysfunction of motor and sensory functions after SCI is caused by the following two processes: primary injury and secondary injury.…”
Section: Introductionmentioning
confidence: 99%